The Impact of Audiovisual Distraction on The Pain Level of Intravenous Infusion For Preschool Children - Muhamad Idris; Imelda Pujiharti; Atik Rustiningsih (Pusat Penelitian dan Pengabdian Masyarakat STIKES Banyuwangi, 2026)
Installing infusion therapy is an invasive procedure carried out by medical personnel on patients who often experience pain. With audiovisual distraction therapy, it is hoped that pain can be reduced during infusion installation, especially for children who are prone to fear, as the impact of trauma on children when infusion therapy is carried out during treatment. This research aims to determine the effect of audiovisual distraction on the pain level of infusion installations in preschool children. This study used a quasy experiment design with a post-test-only non-equivalent control group design approach. Samples were selected using the accidental sampling technique, with a total of 60 preschool children (3-6 years) divided into a control group and a distraction intervention group. Pain levels were measured using the FLACC scale. Data analysis used the Mann-Whitney U-test statistical test. The results showed the effect of audiovisual distraction on the pain level of infusion installation in preschool children with a p value of 0.000. Providing audiovisual distraction therapy is very important as non-pharmacological pain management during IV insertion in children so that children do not experience trauma or fear.